Metode Dan Media Pada Penyuluhan Teknologi Budidaya Padi Sistem Tanam Jajar Legowo 4:1 - Amran, Farizah Dhaifina; Rasyid, Rasmeidah; Riskiana Sam, Besse (Forum Agribisnis, 2024)
The application of technology by farmers is one of the keys to success in increasing crop productivity. Farmers' decisions in adopting this technology are largely determined by the involvement of agricultural extension services regarding the methods and media they use. Carrying out duties as a source of motivation, educator, driver, organizer, communication trainer and counselor for farmers, extension services can influence targets including the use of extension methods and media to communicate and collaborate with farmers to increase farmers' knowledge regarding the jajar legowo 4:1 planting system . The purpose of this study is to examine the most effective extension methods and extension media applied by agricultural extension services and to examine the connection between the effectiveness of extension methods and extension media on the implementation of the Jajar Legowo 4:1 planting method. This research examines the Mamminasata Farmers Group using a case study approach, where this method is a form of research that can be carried out both quantitatively and qualitatively. Quantitative descriptive methods are used to measure the effectiveness of agricultural extension methods and media. Spearman rank analysis was used to measure the correlation and connection between the effectiveness of extension methods and media and the implementation of the Jajar Legowo 4:1 planting system. The research results found that the most effective method used in agricultural extension to maintain or increase rice production is the demonstration plot method and the most effective media is oral media. The results of the Spearman rank analysis find that actual correlation among the implementation of the Jajar Legowo 4:1 planting method cultivation technology and the effectiveness of extension methods and media.